Implementasi Kriptografi pada Email Menggunakan Metode Advanced Encryption Standard dan Rivest Code 4 Berbasis Web - Sulaksono, Danang Haryo; Putra, Juan Yoshep Oktafilia (Prosiding Seminar Nasional Teknik Elektro, Sistem Informasi, dan Teknik Informatika (SNESTIK), 2024)
Computer progress has had a major impact on people's lives, especially in terms of the efficient exchange of information. However, it also brings with it increased security risks, especially when using email, leading to concerns about data loss and tampering. To mitigate these risks, cryptographic security measures have been implemented. Cryptography protects the confidentiality and integrity of data. Two common cryptographic methods were used in this study: Advanced Encryption Standard (AES) and Rivest Code 4 (RC4). AES is a standard algorithm for symmetric key encryption, while RC4 is a stream cipher that processes input data simultaneously. In the study, email messages were sent in plain text, encrypted in ciphertext and decrypted back into plain text using the same algorithm. The test results showed that RC4 had the lowest average CPU load (17.3%) during encryption, while AES had the lowest average memory load (36%). The avalanche effect tests showed a high average value (94.799%) for plaintext and key tests. RC4 also showed the fastest average encryption time (0.608 seconds). These findings indicate that both the AES and RC4 methods are suitable for encrypting email content.